From Portugal to the colonies: characteristics of Portuguese exilies at the end of the 18th century - Neves, Liliana (2021)
The exile penalty has been widely used by the portuguese justice over the past centuries. The exiled were forced to cross the Atlantic in the direction of Brazil, Africa and Asia, where they fulfilled the punishment. The constant sending of large human contingents to colonial territories demonstrates the interests that the Crown had in removing the criminals from the metropolis. However, it can be an indicator of other objectives, such as the population and effective possession of the places where they were destined. This reality caused variations in the fate of the exiles according to the times and the needs that the Crown had in different periods. Thus, several authors agree that the sending of exiles to the colonies was aimed at occupation, defence, settlement and contribution to miscegenation in these territories. Through this research work, we seek to carry out a comparative study where we highlight the differences between the sending of exiles to the South American and African colonial territories. We also seek to get to know these individuals seeking to know their social status, profession, crime, age, marital status, place of birth, destination of exile and time of sentence. It was also our intention to analyze how the process of sending these individuals overseas was carried out, the time between the condemnation and their departure, how they were shipped, who was in charge of taking them to their destination and who guaranteed their survival during the trip.